2018
DOI: 10.1007/s40204-018-0083-4
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic polymeric biomaterials for wound healing: a review

Abstract: Wounds are of a variety of types and each category has its own distinctive healing requirements. This realization has spurred the development of a myriad of wound dressings, each with specific characteristics. It is unrealistic to expect a singular dressing to embrace all characteristics that would fulfill generic needs for wound healing. However, each dressing may approach the ideal requirements by deviating from the ‘one size fits all approach’, if it conforms strictly to the specifications of the wound and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
247
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 419 publications
(256 citation statements)
references
References 164 publications
(188 reference statements)
2
247
0
7
Order By: Relevance
“…Another advantage of this system is that the mechanical properties of the synthetic matrices can be tailored to mimic soft tissues of interest, here in the range of healthy dermis for wound healing applications. Our research is just one example of how hydrogels can be “tuned” for a variety of different therapeutic applications and afford the potential to be molded to any shape of interest for filling defects within injured tissues …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another advantage of this system is that the mechanical properties of the synthetic matrices can be tailored to mimic soft tissues of interest, here in the range of healthy dermis for wound healing applications. Our research is just one example of how hydrogels can be “tuned” for a variety of different therapeutic applications and afford the potential to be molded to any shape of interest for filling defects within injured tissues …”
Section: Discussionmentioning
confidence: 99%
“…Our research is just one example of how hydrogels can be "tuned" for a variety of different therapeutic applications and afford the potential to be molded to any shape of interest for filling defects within injured tissues. 66,67 Integrins are integral membrane proteins that allow cells to sense and interact with their external environment, comprised mainly of ECM glycoproteins and neighboring cells. 68 There are at least 24 integrin heterodimers, each with a unique binding specificity.…”
Section: Discussionmentioning
confidence: 99%
“…Entre los materiales no biodegradables es común el uso de derivados de polietileno, politetrafluoroetileno, polimetilacrilatos, poliacrilamidas, poliéteres, polisiloxanos, poliuretanos, polietilenglicol entre otros [20]. Este tipo de materiales tienen ventajas tales como la no inmunogenicidad, buena reproductibilidad, adecuadas propiedades mecánicas y formas diseñadas a la medida [18].…”
Section: Compuestos Biocompatibles Promotores De Launclassified
“…Recently, Hussain et al systematically reviewed and reported a number of convincing evidences for bioactive materials embedded polymer‐based chronic wound healing modalities, as well as the latest and innovative therapeutic strategies for management of chronic nonhealing wounds (Hussain, Thu, Shuid, Katas, & Hussain, ; Shao et al, ). Related studies also introduced technical solutions in development of different biomaterials used in wounds healings (Mir et al, ; Murray, West, Cowin, & Farrugia, ; Pop & Almquist, ). Figure illustrates the classification of bioactive agent‐based dressings applied to treat CVI.…”
Section: Polymer‐based Functional Wound Dressings For Treating CVImentioning
confidence: 99%